ANALISIS PENGARUH SENSITIVITAS HARGA TERHADAP PERILAKU PEMBELIAN KONSUMEN AVOSKIN DI KOTA PALEMBANG: PENGAPLIKASIAN TEORI PERILAKU TERENCANA - Wulandari, Siska; Lina, Lina; Tyra, Maria Josephine (Forum Bisnis Kewirausahaan, 2025)
This study analyses the influence of TPB and price sensitivity on green purchasing behaviour of Avoskin generation Z consumers and millennials in Palembang, mediated by green purchasing intention. 191 respondents were processed using smart PLS 3. The results of this study found that attitude and behavioural control have a significant positive relationship with Avoskin purchase intention. Behavioural control, subjective norms, and green purchase intentions have a positive and significant effect on consumer green purchasing behaviour. Green purchase intention mediates attitude towards Avoskin green purchasing behaviour, full mediation. Green purchase intention mediates behavioural control on Avoskin's green purchasing behaviour, partial mediation. Keyword: Attitude, Subjective Norm, Behavioural Control, Price Sensitivity, Green Purchase Intention, Green PurchaseBehaviour